MILLENNIALS GREEN AWARENESS - Alamaireh, Moh’d Kheir (Journal of Central European Green Innovation, 2020)
As the huge human dependency on energy sources, the human have developed many technologies in different sectors. Also the infrastructure that developed very fast renewable energy resources crossed huge milestones and developed very fast as well in the past years. Still among people increased awareness and the news sharing trends especially in the social media era, forced many governments, businesses and people to start developing more green alternatives. As the future especially with the current challenges is going to be green, and those who are operating their businesses without a competitive, sustainable and green strategy are most probably going to be kicked out from the market in the near future. The aim of this study curried out at Eszterházy Károly University, Hungary is to observe Millennial from different backgrounds, cultures and experiences as well as fields, green awareness, in addition to that, observing their feedback and thoughts about the challenges, what is causing them, how they can be addressed now as well as in the near future and their understanding of the current governmental, industrial as well as individual efforts that they are being put into action, to measure their willingness to contribute to that and how important do they think those efforts and how much it can help in addressing the problem. The results showed an insufficient understanding of the problems as well as the available solutions to tackle the problems. In addition to that, lack of appreciation to the current efforts put into addressing the problem. Still they showed great willingness to be an active part of the solution even though they have no clear idea of how they can achieve that. Through qualitative interviews and observational methods these conclusions were drawn.